PENERAPAN TEKNIK FACIAL IMAGE COMPARISON DALAM DETEKSI IMPOSTOR PADA PEMERIKSAAN KEIMIGRASIAN - Aulia, Chelnysia Miranda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Globalisation and cross-border mobility pose challenges to immigration oversight, particularly related to the misuse of travel documents by impostors. Visual-based identity verification through facial matching is a crucial method for ensuring document authenticity. This study aims to examine the application of facial image comparison as a supporting instrument in detecting impostors at Immigration Checkpoints (TPI). The method used is descriptive qualitative, with data collection through literature review, document analysis, and visual observation of facial images. The study focused on six main elements: ears, eyes, nose, lips, face and chin shape, and facial markings. The results show that each individual's visual characteristics are unique and therefore can be effective indicators in distinguishing legitimate document holders from impostors. Case studies demonstrate that variations in facial morphology can be used to detect individual differences and similarities, whether due to genetic factors or changes in appearance. This study also emphasises the need to integrate automated systems such as Autogate with the manual observation capabilities of immigration officers to anticipate technical challenges. Thus, the application of facial image comparison is expected to improve the accuracy of identity verification, strengthen immigration oversight, and maintain national security.